Environmental drivers of eukaryotic plankton and fish biodiversity in an Arctic fjord - Virginie Marques; Christel Hassler; Kristy Deiner; Elias Meier; Alice Valentini; Camille Albouy; Loïc Pellissier (Polar Biology, 2023)
Arctic fjords are experiencing rapid environmental shifts due to climate change, which may have significant impacts on marine biodiversity and ecosystem functioning. However, the impact of climate change on fjord biodiversity is difficult to quantify given the low accessibility and high cost to sample these areas. In this study, we sampled locations from inside to outside an Arctic fjord and used environmental DNA metabarcoding to assess how the biodiversity of fish and eukaryotic plankton communities relate with environmental conditions. We detected a total of 12 fish taxa and 872 MOTUs for eukaryotes and found marked gradients of temperature and salinity driven by the distance to the glacier at the terminal part of the fjord and depth. Eukaryotic richness was mainly associated with lower temperature and chlorophyll a . Moreover, co-inertia analyses showed a shared structure between eukaryotes assemblages and the environmental gradients. A partial association between eukaryote and fishes suggest a potential shared effect of environmental gradients among these taxa. Our findings provide a baseline for future studies to assess how these assemblages may be impacted by ongoing environmental changes and highlight how fjord ice loss and warming might shift environmental gradients and species distribution under climate change.